2019
DOI: 10.3389/fpls.2019.00542
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Ideal Allele Combinations for the Adaptation of Spring Barley to Northern Latitudes

Abstract: The northwards expansion of barley production requires adaptation to longer days, lower temperatures and stronger winds during the growing season. We have screened 169 lines of the current barley breeding gene pool in the Nordic region with regards to heading, maturity, height, and lodging under different environmental conditions in nineteen field trials over 3 years at eight locations in northern and central Europe. Through a genome-wide association scan we have linked phenotypic differences observed in multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 71 publications
(115 reference statements)
5
23
0
Order By: Relevance
“…The Icelandic environment poses challenges to crop production by the low temperature during the growth season. An extreme earliness in Icelandic barley lines has previously been reported (Göransson et al 2019). The current study, for the first time, confirms the extreme This article is protected by copyright.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The Icelandic environment poses challenges to crop production by the low temperature during the growth season. An extreme earliness in Icelandic barley lines has previously been reported (Göransson et al 2019). The current study, for the first time, confirms the extreme This article is protected by copyright.…”
Section: Discussionsupporting
confidence: 90%
“…It is interesting that CEN, a wellknown earliness locus, did not show up in the GWAS. However, other studies have reported that a single allele of the CEN locus is virtually fixed in European spring barley (Tondelli et al 2013;Fjellheim et al 2014;Göransson et al 2019) which could explain why it was not found in the GWAS of the currently reported panel.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Thus, our results show that modern Australian barley cultivars are not genetically depauperate in comparison to historical varieties, which counters the common perception that intensive breeding leads to the erosion of adaptive genetic diversity in modern cultivars [1, 2]. This notion is supported by several recent reports on cereal crops such as wheat, which demonstrate that genetic diversity has not been reduced in European wheat cultivars over the past five decades of progress in breeding [24, 25]. Moreover, the faster LD decay and lower level of long-range LD of more recently released cultivars indicate that recent breeding efforts have increasingly integrated lines with more diverse genetic backgrounds into the pool of Australian germplasm.…”
Section: Discussionsupporting
confidence: 75%
“…S9). Crop plants grown under variable environments experience different photoperiod and therefore the influence of the regulator of Hd varies with the environment(Göransson et al 2019;Afsharyan et al 2020). For instance, our lower latitude trials (Turkey, Syria) have less annual variation in photoperiod compared to higher latitude Germany where average day length increases by up to 4 hours during the spring growing season.Furthermore, temperature, humidity and soil type can also influence Hd.…”
mentioning
confidence: 93%